Penelitian Komunikasi Interpersonal Pustakawan Dengan Pemustaka Di Perpustakaan Melalui Database Google Scholer Dan Dimensions : Narrative Literature Review - Annisa, Fitri; Anwar, Rully Khairul; Djen Amar, Siti Chaerani; Rukmana, Evi Nursanti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
AbstractThis study aims to determine how the role of interpersonal communication between librarians and users in libraries through the narrative literature review method with four references taken through the Google Scholer and Dimensions database from 2013 to 2023. The results of this study show that librarians have an important role in interpersonal communication between librarians and users in libraries. Because interpersonal or interpersonal communication is the delivery of information or a message involving two or more people through direct interaction so that it may get verbal or nonverbal reactions that are useful in establishing positive good relationships between librarians and users, avoiding conflicts that may occur due to misunderstandings, and avoiding users from negative perceptions about librarians. In which there are often obstacles such as misperceptions created by users to librarians or vice versa, lack of librarian sensitivity to user needs, and information that has not been conveyed properly. however, it can be straightened out by effective interpersonal communication applied with a librarian skill in understanding the meaning of equality, positivity, supportiveness, empathy, and openness. Keywords: Interpersonal Communication; Users; LibrarianAbstrakPenelitian ini bertujuan untuk mengetahui bagaimana peran komunikasi interpersonal pustakawan dengan pemustaka di perpustakaan melalui metode narrative literature review dengan empat rujukan yang diambil melalui database google scholer dan dimensions dari tahun 2013 sampai 2023. Hasil dari penelitian ini menunjukkan bahwa pustakawan komunikasi interpersonal antara pustakawan dengan pemustaka memiliki peran penting dalam perpustakaan. karena komunikasi interpersonal atau antar pribadi merupakan penyampaian informasi atau suatu pesan melibatkan dua orang atau lebih melalui interaksi secara langsung sehingga mungkin mendapatkan reaksi secara verbal maupun nonverbal yang bermanfaat dalam menjalin hubungan baik yang postitif antara pustakawan dengan pemustaka, menghindari konflik yang mungkin terjadi sebab kesalahpahaman, dan menghindarkan pemustaka dari presepsi negative mengenai pustakawan. Yang dimana didalamnya sering terjadi hambatan seperti kesalahan presepsi yang diciptakan pemustaka terhadap pustakawan atau sebaliknya, kurangnya kepekaan pustakawan terhadap kebutuhan pemustaka, dan informasi-informasi yang belum tersampaikan dengan baik. namun hal tersebut dapat diluruskan dengan komunikasi interpersonal efektif yang diterapkan dengan suatu keterampilan pustakawan dalam memahami arti dari adanya kesetaraan (equality), Rasapositif (positiveness), Dukungan (supportiveness) Empati (empathy), dan Keterbukaan (openness).Kata Kunci: Komunikasi Interpersonal; Pemustaka; Pustakawan